Characteristics of Individuals Who Receive Pharmacotherapy While in Treatment For Opioid Use Disorder in the United States. (June 2020) - Mutter, Ryan; Feder, Kenneth A.; Ali, Mir M.
Abstract : Objective: Treatments that include pharmacotherapy are the standard of care for opioid use disorder (OUD), but they are underutilized. This paper uses a large sample of treatment admissions for OUD in the United States to examine characteristics predictive of receiving treatments that include pharmacotherapy. Methods: Data come from the 2014 Treatment Episode Dataset—Admissions. Generalized linear regression models were utilized to assess the association of receiving pharmacotherapy treatment with a number of demographic, treatment, and disorder characteristics. Results: Less than one third of treatment admissions for an OUD involved pharmacotherapy. Among the factors most associated with receiving pharmacotherapy treatment were referring oneself to treatment, as opposed to a medical or nonmedical professional, and receiving treatment in a nonintensive outpatient setting, as opposed to intensive outpatient or residential settings. Conclusion: Encouraging professionals to refer clients to programs that offer treatments that include pharmacotherapy, and incorporating pharmacotherapy into a greater diversity of treatment settings, could help increase access to evidence-based care for OUD. Abstract : Supplemental Digital Content is available in the text.